Problems of empire - Marshall, P. J. (Peter James), author.
1 online resource (239 pages)
Keywords: The volumes in this set, originally published between 1968 and 1989, draw together research by leading academics in the area of the British Empire and provides an examination of related key issues. The volumes examine slavery in the British Empire, problems encountered in India in the eighteenth and nineteenth century, as well as the Empire at its most powerful. This set will be of particular interest to students of British, colonial, and world history.